Analisa Hukum Klausul Eksonerasi (Pembebasan Tanggung Jawab) dalam Akta Notaris - Claudia Manibuy (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
The exoneration clause was born in a notary deed due to notary concerns from the actions of clients who had bad faith in making a deed before a notary. The inclusion of this clause raises questions regarding its legality, considering that the substance of the notarial deed in accordance with the provisions of the UUJN only contains the interests of the parties. This research uses normative juridical methods. The results of this study explain that the exoneration clause in legality does not violate the UUJN and does not eliminate the identity of the deed, provided that the inclusion of the clause must be based on the information of the parties that the documents submitted as deed making data are true, and do not involve notaries from all forms of legal cases due to matters caused by the parties themselves, Furthermore, the information or statement is constantized by the notary in the deed. Although, the existence of this clause does not mean that the notary can be exempted from all forms of legal entanglement if it is proven that the notary has manifestly committed an offense and caused losses to the parties in the deed. Keywords: Legality; Exoneration Clause; Notary Deed.